2011
DOI: 10.1097/brs.0b013e3182077122
|View full text |Cite
|
Sign up to set email alerts
|

Does Lumbar Disc Degeneration on Magnetic Resonance Imaging Associate With Low Back Symptom Severity in Young Finnish Adults?

Abstract: Intervertebral DD was associated with low back symptom severity among young adults, suggesting that the symptoms may have a discogenic origin at this age. However, DD was also found in one-third of asymptomatic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(137 citation statements)
references
References 51 publications
2
133
1
1
Order By: Relevance
“…The strong associations found here between disc degeneration and uneven intervertebral motion in patients, but not in controls, seem consistent with this. It is also consistent with other recent research, which found that disc degeneration was associated with low back pain, especially when associated with end-plate signal change [11,44,45]. However, unlike the present work, these studies used MRI disc degeneration grading, while radiographic grading based on structural aspects rather than biochemical changes may be better correlated with pain when considered alongside intervertebral motion patterns.…”
Section: Discussionsupporting
confidence: 91%
“…The strong associations found here between disc degeneration and uneven intervertebral motion in patients, but not in controls, seem consistent with this. It is also consistent with other recent research, which found that disc degeneration was associated with low back pain, especially when associated with end-plate signal change [11,44,45]. However, unlike the present work, these studies used MRI disc degeneration grading, while radiographic grading based on structural aspects rather than biochemical changes may be better correlated with pain when considered alongside intervertebral motion patterns.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, many of those with LBP suffer from disability (1). Multiple causes could lead to LBP; however, intervertebral disc degeneration (IDD) and disc herniation are reported to be the two most common diagnoses and targets for intervention (2), with IDD being deemed as the main cause of LBP (3,4). IDD is a multifactorial process that is characterized by cellular and biochemical changes in the disc tissue, consequently generating structural failure (5).…”
Section: Introductionmentioning
confidence: 99%
“…Disc degeneration is markedly common, but a definitive and widely accepted definition remains unclear. In clinical studies using MRI, disc degenera-tion has been suggested to be one of the most remarkable risk factors for discogenic low back pain [60][61][62][63] . Many papers identified genetic influences and unidentified factors, which include complex and unpredictable interactions for the presence of disc degeneration, besides, disc degeneration might not be induced by most environmental factors [64][65][66][67][68] .…”
Section: Mechanical Hypermobilitymentioning
confidence: 99%